2019
DOI: 10.1111/cge.13633
|View full text |Cite
|
Sign up to set email alerts
|

Causative and common PHOX2B variants define a broad phenotypic spectrum

Abstract: Paired Like homeobox 2B (PHOX2B) is a gene crucial for the differentiation of the neural lineages of the autonomic nervous system (ANS), whose coding mutations cause congenital central hypoventilation syndrome (CCHS). The vast majority of PHOX2B mutations in CCHS is represented by expansions of a polyalanine region in exon 3, collec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 87 publications
0
36
0
Order By: Relevance
“…Trasmission of CCHS is autosomal dominant with variable expressivity and incomplete penetrance, and without any gender preference (Weese-Mayer et al, 2003;Bachetti and Ceccherini, 2020). Variable CCHS-like phenotypes have been reported associated with whole and partial gene deletions of PHOX2B as extensively reported (Jennings et al, 2012;Bachetti and Ceccherini, 2020).…”
Section: Congenital Central Hypoventilation Syndrome (Cchs): Clinicalmentioning
confidence: 91%
See 2 more Smart Citations
“…Trasmission of CCHS is autosomal dominant with variable expressivity and incomplete penetrance, and without any gender preference (Weese-Mayer et al, 2003;Bachetti and Ceccherini, 2020). Variable CCHS-like phenotypes have been reported associated with whole and partial gene deletions of PHOX2B as extensively reported (Jennings et al, 2012;Bachetti and Ceccherini, 2020).…”
Section: Congenital Central Hypoventilation Syndrome (Cchs): Clinicalmentioning
confidence: 91%
“…The variable phenotypes reported in CCHS patients carrying the same mutation also suggest the involvement of modifier genes of expressivity (Di Lascio et al, 2018a;Bachetti and Ceccherini, 2020). Mutations in genes other than PHOX2B, involved in the differentiation of neural crest cells (RET, GDNF, BDNF, GFRA1, PHOX2A, HASH-1, EDN1, EDN3, BMP2) or in oncogenes (BRAF) (Bolk et al, 1996;Amiel et al, 1998;Weese-Mayer et al, 2002Sasaki et al, 2003;Fernández et al, 2013;Al Dakhoul, 2017) have been found in some CCHS individuals.…”
Section: Congenital Central Hypoventilation Syndrome (Cchs): Clinicalmentioning
confidence: 96%
See 1 more Smart Citation
“…Familial cases with CCHS exist [ 22 , 45 , 46 , 48 , 53 , 86 , 95 ], due to parental transmission of somatic and germline mosaic mutations [ 6 , 9 , 72 ]. In the meantime, PHOX2B -mediated mechanisms have been extensively investigated and better understood in vitro [ 4 , 5 , 7 , 8 , 20 , 24 , 25 , 68 , 97 ], in vivo [ 27 , 44 , 70 ], and in CCHS patients [ 28 , 33 , 92 94 , 99 ]. However, most pathogenic pathways are yet to be disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐exome sequencing, which covers the 1% to 2% of the genome that encodes proteins, is somewhat a misnomer, as it does not completely cover the entire exome, and different methodologies may have different gaps. Whole‐exome sequencing will also not identify small repeat expansions, such as in PHOX2B (congenital central hypoventilation 13 ). Probably more important, current clinical, or medical whole‐exome studies generally only report variants in the ~20% of genes known to be associated with the disease.…”
Section: Introductionmentioning
confidence: 99%